Wireless ultra-reliable and low-latency communication:key design analysis and challenge - Yusun FU; Genke YANG (Tongxin xuebao)
The current fragmented ultra reliable and low latency communication (URLLC) research focusing on a certain point was overcome.From the perspective of panoramic view,starting from the application scenarios and requirements,the system architecture,key technologies and solutions of URLLC were analyzed and introduced.Then,the physical layer detection performance requirements,link adaptation,radio resource management,end-to-end diversity solutions and how to integrate with TSN (time sensitive network) were analyzed in depth,and possible candidates were discussed.It hopes to have a thorough and comprehensive understanding of the theoretical research and application of URLLC,and a clear understanding of its challenges,so as to play a key reference for researchers and engineers in the related fields.